KOREOGRAFI PELUK JIWA KARYA JONET SRI KUNCORO DAN MT. WASI BANTOLO BERSAMA ANAK DISABILITAS TUNA RUNGU - Wardanny, Smirna; Widyastutieningrum, Sri Rochana (Greget : Jurnal Kreativitas dan Studi Tari, 2023)
This study describes the process of creation and form of Peluk Jiwa dance. The problems in this study include process of creating Peluk Jiwa dance choreography and form of Peluk Jiwa dance. The choreography of Peluk Jiwa is based on the traditional Surakarta style dance movements that are balanced and adapted to the abilities of the dancers who are deaf children, non-disabled children and physically disabled singers. The dance work Peluk Jiwa tells about social equality between normal people and people with physical disabilities. This study uses a qualitative method that is descriptive analysis. The theory used to solve the problem of the choreography creation process uses a theory with seven stages, namely elements of dance moves, theme selection, technique, exploration, organization, unity, presentation while to dissect the form of the work of Peluk Jiwa Dance using nine main elements including (1) dance title, (2) dance themes, (3) types of dance, (4) dance room, (5) dance moves, (6) dance music, (7) presentation methods, (8) dancers, (9) makeup and clothing. The results of this study indicate that Peluk Jiwa Dance is the work of Jonet Sri Kuncoro and Wasi Bantolo with children hearing impairments who were created through a seven-stage creative process and also added that the form of Peluk Jiwa is a drama dance involving dancers for children with hearing impairments. This work contains a message of social equality between children with hearing impairments and normal children.